Nivolumab treatment beyond RECIST‐defined progression in recurrent or metastatic squamous cell carcinoma of the head and neck in CheckMate 141: A subgroup analysis of a randomized phase 3 clinical trial. Issue 18 (27th June 2019) - Haddad, Robert; Concha‐Benavente, Fernando; Blumenschein, George; Fayette, Jerome; Guigay, Joel; Colevas, A. Dimitrios; Licitra, Lisa; Kasper, Stefan; Vokes, Everett E.; Worden, Francis; Saba, Nabil F.; Tahara, Makoto; et al.
Abstract : Background: Response patterns with immune checkpoint inhibitors may be different from those with chemotherapy. Therefore, assessment of response to immunotherapy with the Response Evaluation Criteria in Solid Tumors (RECIST), version 1.1, could result in premature treatment termination. The randomized, open‐label, phase 3 CheckMate 141 trial (NCT02105636), which evaluated nivolumab in recurrent/metastatic squamous cell carcinoma of the head and neck after platinum therapy, allowed treatment beyond first RECIST‐defined progression (TBP) according to protocol‐specified criteria. Methods: In CheckMate 141, patients with RECIST‐defined progression who had a stable performance status and demonstrated clinical benefit without rapid disease progression were permitted to receive TBP with nivolumab at 3 mg/kg every 2 weeks until further progression, which was defined as an additional ≥10% increase in tumor volume. This post hoc analysis evaluated outcomes for patients who received TBP with nivolumab. Results: Of 240 patients randomized to nivolumab, 146 experienced RECIST‐defined progression. Sixty‐two of these patients received TBP, and 84 discontinued treatment (no TBP). Among the 60 TBP patients evaluable for response, 15 (25%) had no change in their tumor burden, and 15 (25%) had reductions in target lesion size; 3 patients (5%) had reductions >30%. The median overall survival among TBP patients was 12.7 months (95% confidence interval, 9.7‐14.6 months). No new safety signals were observed with TBP. Exploratory analyses of immune cell biomarkers suggested a potential relationship with initial and TBP responses. Conclusions: Tumor burden reduction was noted in a proportion of patients who received TBP with nivolumab in CheckMate 141. Additional research is warranted to identify factors predictive of a TBP benefit in this population. Abstract : In the randomized, open‐label, phase 3 CheckMate 141 trial in patients with recurrent/metastatic squamous cell carcinoma of the head and neck after platinum therapy, patients with a stable performance status and the potential for clinical benefit were permitted to receive treatment beyond first Response Evaluation Criteria in Solid Tumors–defined progression (TBP) with nivolumab; tumor burden reduction was noted in a proportion of these patients. Additional research is warranted to identify factors predictive of benefit with TBP in this population.